The relationship of the work pressure with self evaluation of the sport teachers in the middle school - حرباش, براهيم; مقراني, جمال; جغدم , بن ذهيبة; بن زيدان, حسين; فغلول, سنوسي (Journal of Sport Science Technology and Physical Activities, 2017)
The research aim to show the level of the work pressure of sport teachers in the school according to the gender differences, also to measure the self evaluation. In addition to know if there are statistical differences to measure the work pressure of teacher of sport, paying attention to gender with the self evaluation. the survey of relationship between the two measures, While the test has examined that there is a relationship between the work pressure and the self evaluation of the teacher of sport in the school for that reason, the descriptive method focuses on theoretical on manner .The sample was 50 teachers of Mostaganem and Relizane. We took Mohammed Hassan alawi in work pressure and Rosenberg as tool to measure the self evaluation, in addition to that, the statics which were the percentage and the examination of the differences, and Person coefficient. The result showed that the level of the work pressure male teacher is higher than female .This means that there are differences in gender .whereas, the self evaluation was higher for both of them, with the affirmation of the relationship and controversial attachment between the two measures of work pressure and self evaluation. As the students concluded that the amelioration of the image of sport through training and reducing the level of the work pressure of the teacher to realize the educative purpose and interest.